Sodium Benzoate Attenuates Secondary Brain Injury by Inhibiting Neuronal Apoptosis and Reducing Mitochondria-Mediated Oxidative Stress in a Rat Model of Intracerebral Hemorrhage: Possible Involvement of DJ-1/Akt/IKK/NFκB Pathway - Xu, Weilin; Li, Tao; Gao, Liansheng; Lenahan, Cameron; Zheng, Jingwei; Yan, Jun; Shao, Anwen; Zhang, Jianmin (Frontiers in Molecular Neuroscience, 2019)
Intracerebral hemorrhage (ICH) is a devastating disease with high rates of mortality and morbidity. The aim of this study was to explore whether Sodium Benzoate (NaB) could reduce neural cell apoptosis and alleviate neurological deficits after ICH. To assess the therapeutic effects of NaB, first, we measured brain water content, neurobehavior, and blood-brain barrier (BBB) integrity at 24 h after ICH in different groups. Then western blot and immunofluorescence staining (IF) were applied to test the levels of different proteins. Transmission electron microscope (TEM) was used to observe ultra-structures within the cells in different groups. The results showed that levels of DJ-1, p-Akt and p-IκB kinase (IKK) increased after ICH and peaked at 24 h. Besides, NaB significantly upregulated DJ-1 in both cytoplasm and mitochondria, and also increased the levels of p-Akt, p-IKK and Bcl-2/Bax ratio, but decreased the levels of caspase-3 and caspase-9. Additionally, NaB decreased reactive oxygen species (ROS) while increased adenosine triphosphate (ATP), which then improving the neurological functions at 24 h and long-term (21 days) memory and spatial learning ability after ICH. However, the results mentioned above could be greatly reversed by MK2206 and rotenone. Therefore, we concluded that NaB could attenuate secondary brain injury via inhibiting neuronal apoptosis and reducing mitochondria-mediated oxidative stress via DJ-1/Akt/IKK/NFκB pathway.